Democratic incongruities representative democracy in britain - Judge, David; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Clear disparities exist between notions of representative democracy and political practice in Britain. Alternative models of democracy, however, have their own incongruities in trying to marry representation and democracy. This book analyses the mismatches in democratic theories and between theory and practice in British representative democracy.
Keywords: Science; Science; Science, general